2017
DOI: 10.22608/apo.201735
|View full text |Cite
|
Sign up to set email alerts
|

Two-Port Pars Plana Anterior and Central Core Vitrectomy (Lam Floaterectomy) in Combination With Phacoemulsification and Intraocular Lens Implantation Under Topical Anesthesia for Patients with Cataract and Significant Floaters: Results of the First 50 Consecutive Cases

Abstract: The 3-month results in terms of safety and efficacy of the Lam floaterectomy in combination with phaco and IOLfor patients with cataract and significant floaters under topical anesthesia are encouraging. Further larger-scale, prospective, multicenter studies seem warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Although there are reports of topical anesthesia for vitrectomy, their use is limited to symptomatic floaters, and using 27 G instruments. 19 , 20 So far, local anesthesia is still an alternative and a safe procedure compared to general anesthesia, as also shown in other studies. 21…”
Section: Discussionmentioning
confidence: 66%
“…Although there are reports of topical anesthesia for vitrectomy, their use is limited to symptomatic floaters, and using 27 G instruments. 19 , 20 So far, local anesthesia is still an alternative and a safe procedure compared to general anesthesia, as also shown in other studies. 21…”
Section: Discussionmentioning
confidence: 66%
“…9 Recent studies have shown that local anesthetics that include lignocaine , amethocaine and bupivacaine are effective in providing topical and local anesthesia for intraocular surgery and Instillation of these local anesthesia decreases intraocular pressure (IOP) transiently . 12,8,5,13 As the duration of anesthesia and analgesia is very brief by these drugs , it requires repeat instillation of drops in the conjuctival sac after every 30 minutes but long-term use of these topical drugs is associated with ocular surface toxicity as they contain preservatives like benzalkonium chloride Most of the patients were in their fifth and sixth decade of life when they underwent 23 gauge three port pars removal of sillicone oil. The peribulbar technique for local anesthesia is a type of block that has been introduced and developed as ocular and periocular anesthetic technique for surgical procedures recently.…”
Section: Discussionmentioning
confidence: 99%
“…4 Apart from vitreo retinal procedures , topical anesthesia is also used in routine phacoemulsification procedures and ocular surgeries like trabeculectomy and pterygium excision . 5 Conventional 20-guage, 23-guage, and 25-guage sutureless pars plana vitrectomies have been performed under topical anesthesia in view of their early visual rehabilitation and good analgesic effect for the procedure. Mahajan et al have studied the effect of topical versus peribulbar anesthesia for patients undergoing pars plana vitrectomy for vitreous hemorrhage and found that the pain score between the two groups was almost similar with the only difference that in topical anesthesia group the maximum pain during the procedure is felt at the time of trocar insertion whereas in the peribulbar block it is felt at the time of local anesthesia being given but the topical anesthesia does not cause lie edema and conjuctival chemosis that is seen in routine patients with peribulbar anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…There was no obvious explanation to their visual symptoms. Floaterectomy may help in the second patient but it carries certain risks [ 12 ]. Agarwal et al [ 11 ] believed the pinhole accentuates even small-medium vitreous opacities and creates such visual disturbance.…”
Section: Discussionmentioning
confidence: 99%